Phenotypic changes in pseudomonas aeruginosa induced by sub-inhibitory exposure to chlorohexidine - Haji, Sayran Hamad; Aka, Safaa Toma (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Many bacterial isolates show an increased antimicrobial resistance due to biofilm production. Repeated exposure to sub lethal concentrations of antimicrobial agents certainly contributes to the resistance as compared to planktonic bacteria. The aim of this study was to test whether the bacterial phenotypes of P. aeruginosa can be changed during exposures to the concentrations at sub lethal doses of chlorhexidine. Methods: Sheep blood agar plates were used for evaluation of haemolysin assay for isolates of P. aeroginusa. A 96-flat bottom well microtiter plates were used for determination of MIC of antibiotic and biofilm formation. Results: All tested isolates were able to lyse RBCs after exposure to sub-MIC of chlorhexidine. Effectiveness of sub-lethal doses of chlorhexidine on biofilm formations varied depending on the contact time. In general, long contact time exhibited increasing biofilm than short time. No significant difference in biofilm was detected among contact times: day I, day II and day III (P = 0.132, P = 0.139 and P = 0.125, respectively). The most effective sub-MIC of CHX was against azithromycin, since the resistance increased significantly (P = 0.008). Conclusion: Surviving P. aeruginosa to low concentration of chlorhexidine can exhibit stronger biofilm and increased resistance to antibiotics.